Tailoring Infographics on Water Resources Through Iterative, User‐Centered Design: A Case Study in the Peruvian Andes. Issue 2 (1st March 2020) - Grainger, Sam; Ochoa‐Tocachi, Boris F.; Antiporta, Javier; Dewulf, Art; Buytaert, Wouter
Abstract: Effective communication and knowledge sharing across stakeholder groups (e.g., science, government, business, civil society, farmers, and the general public) are essential for more informed water resource management. Visualizations and graphics are powerful tools to engage diverse groups with unfamiliar information. Despite this potential, the design of visuals within applied science settings often does not involve end‐user interaction or explicit consideration of their existing knowledge systems, perspective, requirements, and context of use. As a result, products are often difficult for users to understand and contextualize. While user interaction and the development of tailored visualizations is increasingly promoted as a potential remedy, limited empirical evidence exists that shows the potential impact and can guide the development of specific approaches. We piloted an iterative and user‐centered design methodology toward the tailoring of infographic‐style posters in the context of Peruvian water governance. To test whether tailoring demonstrably improves the perceived effectiveness of products, we designed three products that conveyed similar information but were tailored to three different audiences (an Andean agricultural, urban professional, and urban general). We then compared the tailored posters to those tailored to other audiences by means of interviews and user grading. We found that end‐users perceive products that have undergone tailoring as more interesting, clearer, and more useful than products designed without explicit user consideration. Our findings indicate that identifying groups with shared characteristics and requirements is key for effective tailoring. Our research provides empirical evidence to support the incorporation of user‐centered design methods in water resource management contexts. Plain Language Summary: Communication of science‐based information to nonscientists is essential to inform water resource management. Visualizations and graphics are powerful tools to engage people with unfamiliar information. Considering audiences explicitly, and directly consulting with them, may improve information uptake and understanding. Therefore, the production of tailored visuals developed for (and in consultation with) specific people or groups of people (e.g., engineers and policy makers) is increasingly being promoted to enhance knowledge sharing within environmental management. However, as yet, there is little scientific evidence to support its practical implementation. To address this, we trialed an iterative and user‐focused approach to tailoring with the aim to provide three different posters, communicating similar information, to three different groups of people interested in Peruvian water resources management. At the end of the design process, we asked people from each group to evaluate all three posters to see if the poster tailored to them was more effective than the other two. We find evidence that target users perceive products that have undergone tailoring as more interesting, clearer, and more useful than products designed without consideration of their representative group. Our findings indicate that tailoring can be particularly effective when people within a target group share similar characteristics and requirements. Key Points: An iterative and user‐centered methodology for appropriate tailoring of infographics is tested in the context of Peruvian water governance Visual products designed with explicit user consideration (tailoring) are perceived as more interesting, clearer, and more useful A key challenge for tailoring is identifying groups with shared characteristics and requirements